METHODOLOGY AND ICONIC AND CONVENTIONAL CODES: «SLAVIC MYTHOLOGY» BY MYKOLA KOSTOMAROV - Soletskyi, Oleksander (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
Objective. The article examines the peculiarities of the methodology of M. Kostomarov’s work "Slavic Mythology." It determines the role of interpretations of iconic and conventional codes of the ancient mythos for theoretical generalizations. It is indicated that M. Kostomarov’s study "Slavic Mythology" is still relevant today, and the author identifies the works that show significant theoretical and methodological influences of the Ukrainian scientist. The article describes the significance of syncretic cooperation of the processes of visual associativity and their influence on the initial verbalization in M. Kostomarov’s research. Research methodology. The study uses a system of genetic, hermeneutic, structural, and semiotic methods. The author relies on the scientific methodology of semiotics and hermeneutics and uses the methodology of literary cognitive science. This is due to the specifics of the study, its object, and its subject. Results. The elevation of the idea of "symbolization" in M. Kostomarov to a methodological principle was based on a transparent interpretive system, where consistent interpretations of iconic and conventional syncretisms of Slavic mythology played the leading role. Ukrainian scholars constantly emphasized that Slavic sacred mythology is not pantheism but a multi-hypostatic and polynomial reflection of divine unity. This iconic and conventional manifestation denotes various forms of sensitization and identification of the light, solar, water, and earthly elements. Different nominations of pagan idols are only variants of designating one of the naturalistic forms of the divine essence.